Chalkstone Vessels from Sepphoris: Galilean Production in Roman Times - Sherman, Maya (Bulletin of ASOR, 2020)
Stone vessels were used in Judaea and the Galilee from the second half of the 1st century b.c.e. until the 2nd century c.e., when it is widely accepted that they were phased out. This study focuses on the major types of chalkstone vessels uncovered in Roman Sepphoris, identifies the unique forms in the assemblage, and discusses the technological issues pertaining to their production. The findings presented in this study suggest that the stone vessels in the Galilee, unlike those in Judaea, did not disappear immediately but were found in layers associated with the Late Roman period (mid-2nd to 4th centuries), thus indicating their continual use. In tracing the sources of the chalkstone vessels, the geochemical analysis employed in this study shows that large numbers of vessels used by Sepphoreans were evidently produced in local quarries of the Lower Galilee.